Intellectual Humility and Self-Censorship in Higher Education; a thematic analysis - Godfrey, Hayden (Frontiers in Education, 2023)
Introduction This article explores whether social science lecturers and postgraduate students perceive their experiences of university as supporting intellectual humility – a concept representing a disposition to rigorously consider opposing ideas to beliefs held in order to confirm the positive epistemic status (or truth) of ones’ own beliefs. Methods Forty participants, consisting of twenty lecturers and twenty postgraduate students from the United Kingdom, took part in semi-structured interviews. The focus of these interviews was to explore whether their experiences in higher education align with the virtue of ‘intellectual humility’. Results Through a thematic analysis, results showed that experiences of both lecturers and students did not support the traits of intellectual humility. Discussion Suggestions for future research are made. The themes identified in this study could be used as a framework for investigating differing contexts of higher education in terms of their reflection of intellectual humility. Further, suggestions for how intellectual humility can be practically facilitated in higher education are made.